Orofacial manifestations of the Levy-Hollister syndrome - Costa, Denis Damiao; Duplat, Candice Belchior Silva; Mariano, Mariana Mota Campos; Nascimento, Bruno Campos; Maia, Caroline Chaves; Falcao, Antônio Fernando Pereira (Journal of Oral Diagnosis, 2016)
The Levy–Hollister syndrome, also known as the lacrimo-auriculo-dento-digital (LADD) syndrome, shows different phenotypes, resulting in a variety of local and systemic signs and symptoms. It is a rare hereditary disorder that mainly causes lacrimal, auricular, and auditory apparatus disturbances and dental and digital anomalies. Here, we describe a case of the Levy–Hollister syndrome in a 24-year-old woman and focus on its orofacial manifestations. The patient had chronic lacrimation, low-set ears, thumb agenesis, elbows with limited pronation and supination movements, pronounced hallux on the left foot, concave facial profile, and tooth roots with atypical morphology.The case emphasizes the importance of a multidisciplinary approach for early diagnosis of the Levy–Hollister syndrome.